2019
DOI: 10.35631/ijlgc.416002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring E-Participation Policy and Initiatives in Malaysia

Abstract: The evolution of Information and Communication Technology (ICT) and the internet have affected the cultural, social, economic and political aspect throughout the world. It also greatly reshaped public administration in the last decade. The availability of internet and electronic medium also open a huge opportunity for the public to participate and become closer to the government. A new form of two-way communication for public and government officials have been developed and changed the landscape of local democ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The findings of the study revealed that none of the websites allowed users/residents to vote on or co-create projects and services. This finding is compatible with Khadzali and Zan (2019), MDEC (2017) and Salamat et al (2011), as there is a serious lack of Malaysian e-government platforms that effectively emphasise e-decision-making. Especially on the ProBE 2016 report, where the item of “presence of e-decision-making: publish outcome of citizen feedback on services/national strategy/policy” ranked the last (only 5% of the total of 622 websites complied with) among the 64 items assessed (MDEC, 2017, p. 10).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The findings of the study revealed that none of the websites allowed users/residents to vote on or co-create projects and services. This finding is compatible with Khadzali and Zan (2019), MDEC (2017) and Salamat et al (2011), as there is a serious lack of Malaysian e-government platforms that effectively emphasise e-decision-making. Especially on the ProBE 2016 report, where the item of “presence of e-decision-making: publish outcome of citizen feedback on services/national strategy/policy” ranked the last (only 5% of the total of 622 websites complied with) among the 64 items assessed (MDEC, 2017, p. 10).…”
Section: Discussionsupporting
confidence: 75%
“…The ProBE focuses on evaluating e-government websites from a provider-centric perspective, JSIT 25,1 whereas MUSE concentrates on public surveys on user satisfaction. Since the ProBE egovernment assessment of the three levels of federal, state and local government websites in 2016, there have been no updated or later editions of the assessment (Khadzali and Zan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Putrajaya itself was built based on the vision to make it a smart green city (Lim et al, 2021). The integration of ICT into the aspects of urban life and smart dimensions in Putrajaya can be viewed, among others, through e-Participation as the realisation of the smart government dimension (Khadzali & Md Zan, 2019;Lim & Yigitcanlar, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Citizens with a voice on their communities' wellbeing tend to be more participative in the mitigation and adaptation efforts proposed. As indicated in the study reported by Khadzali and Md Zan [61], the Malaysian government has invested in various participation platforms. However, these platforms do not provide the citizens with enough power to voice their opinions by setting participating rules and restrictions.…”
Section: Climate Change Mitigation and Adaptation In Urban Malaysia-i...mentioning
confidence: 99%